The Value of Education in Kaba Siti Kalasun by Syamsuddin ST. Radjo Endah - Finasti, Anugrah Anggun; Nursaid, Nursaid; Suhaili, Samsudin; Ningsih, Ayu Gustia; Noveria, Ena (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the educational values ​​of the Siti Kalasun kaba using a sociological study of literature. The educational values ​​in question are the values ​​of faith and piety, aesthetic values, and the value of living together. The data source was obtained directly from Kaba Siti Kalasun herself. The type of research used is qualitative research with descriptive research methods. This research promotes understanding of the empirical interactions between the concepts being researched. This research reveals the educational values ​​in Kaba Siti Kalasun: as individuals, they demonstrate qualities such as love, patience, gentleness, and a life-oriented mindset; as members of society, they are characterized by their relationships with the environment and other people, along with a marked concern for the well-being of the environment and other people.